25x^2 - 60x + 36 = 0 polynomials chapter
Answers
Answered by
1
Answer:
(5x-6)^2
Step-by-step explanation:
25x^2-60x+36
=(5x)^2 - 2(5x)(6) + (6)^2
=(5x-6)^2
Hope it helps
Answered by
6
Good Question Mate...
Answer:- ![\frac{60}{50}=\frac{6}{5}=1.2 \frac{60}{50}=\frac{6}{5}=1.2](https://tex.z-dn.net/?f=%5Cfrac%7B60%7D%7B50%7D%3D%5Cfrac%7B6%7D%7B5%7D%3D1.2)
First we will check that this quadratic equation have real roots or not.
Discriminant⇒b²-4ac ,where a=25, b=(-60), c=36
⇒(-60)²-4(25)(36)
⇒3600-4(900)
⇒3600-3600
⇒0
∴ b²-4ac=0 that means this equation have real and equal roots.
This Quadratic Equation is solved in the Attachment.
Attachments:
![](https://hi-static.z-dn.net/files/ddf/6efda24ea2ad5f92beec7bd4ba747e14.jpg)
Similar questions